Cataloguing and management of major diseases of monopodial orchids - Meera T M (Department of Plant Pathology, College of Horticulture, 2012)
Disease is one of the major production constraints in orchid cultivation. Hence an investigation has been undertaken to study the symptomatology, etiology and management of various diseases of important monopododial orchids viz., Phalaenopsis, Vanda (Basket Vanda), Mokara and Arachnis. A survey was conducted in different locations of Thrissur District viz., orchidarium of AICRP on Floriculture Improvement, Department of Pomolgy and Floriculture, COH, Vellanikkara, nurseries at Cheroor, Thrissur, Perinjanam, Madakkathara and Kanimangalam. Different fungal and bacterial diseases were observed and isolation of pathogen yielded eleven fungal pathogens and two bacterial pathogens. The pathogenicity of these organisms was proved by artificial inoculation. Symptomatology of various diseases was studied in detail under natural and artificial conditions. Fusarium sp. caused wilt symptom in Phalaenopsis and caused leaf spot in Arachnis. Sclerotium sp. caused collar rot in Phalaenopsis and dry rotting in Basket Vanda, Anthracnose pathogen, Colletotrichum sp. produced different symptoms in Phalaenopsis, Mokara and Arachnis. In Phalaenopsis, the symptom was irregular sunken spot, in Mokara leaf blighting and in Arachnis, round sunken spot. Heart rot was the symptom of Phytophthora infection in Basket Vanda. Botryodiplodia leaf spot of Basket Vanda was characterized by greyish white coloured spot with black margin and pycnidia at the centre. Alternaria leaf spot of Mokara, was round to oval shaped with a vertical splitting through the centre of the spot. Soft rot of Phalaenopsis by Erwinia sp. and bacterial wilt of Basket Vanda by Burkholderia sp. were the bacterial diseases observed during the survey. Water soaking and rotting of leaves were the symptoms of soft rot while yellowing, wilting and leaf detachment were the symptoms of bacterial wilt. Cultural characters and morphological characters of fungal pathogens were studied and they were identified at species level. Cultural, morphological and gram reaction of bacterial pathogens were studied and they were identified at species level by molecular techniques. For the management of fungal pathogens, an in vitro evaluation was conducted with fungicides and liquid formulation of Pseudomonas fluorescens. Most of the fungicides revealed cent per cent inhibition on the growth where as P. fluorescens showed 53 - 86 per cent inhibition. For the management of bacterial pathogens, an in vitro evaluation was conducted with cowdung, liquid formulation of P. fluorescens, cowdung + P. fluorescens and Streptocycline and differences were observed in their inhibitory properties. Seasonal influence on the incidence of diseases of monopodial orchids was studied for one year. Influence of temperature, humidity and rainfall was prominent in the incidence of Fusarium wilt, collar rot and soft rot of Phalaenopsis whereas not very prominent in the incidence and severity of Botryodiplodia, Alternaria and Fusarium leaf spot diseases of Basket Vanda, Mokara and Arachnis respectively . Incidence of Fusarium wilt was more in the month of November, collar rot in the month of December whereas bacterial soft rot was prominent in rainy months.